2011
DOI: 10.1039/c1cc13306c
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and isolation of shikimic acid from Ginkgo biloba leaves utilizing an ionic liquid that dissolves cellulose

Abstract: Shikimic acid, the starting material in the commercial synthesis of oseltamivir phosphate (Tamiflu®), was efficiently extracted and isolated from Ginkgo biloba leaves utilizing the ionic liquid 1-butyl-3-methylimidazolium chloride ([bmim]Cl), which dissolves cellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 25 publications
0
45
0
1
Order By: Relevance
“…Meanwhile, ILs have been used as extraction solvent to dispose of plant materials for extraction of components, such as alkaloid [35, 36], procyanidins [37, 38], flavonoid [26], glycoside [27], lignan [39], and coumarin [25]. Recently ionic liquid 1-butyl-3-methylimidazolium chloride has been used for extracting shikimic acid from Ginkgo biloba leaves due to dissolve cellulose at high temperature 150°C [40]. However, to our knowledge, there are no reports on the extraction of cyclitol using ionic liquid aqueous solution utilizing room temperature technology.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, ILs have been used as extraction solvent to dispose of plant materials for extraction of components, such as alkaloid [35, 36], procyanidins [37, 38], flavonoid [26], glycoside [27], lignan [39], and coumarin [25]. Recently ionic liquid 1-butyl-3-methylimidazolium chloride has been used for extracting shikimic acid from Ginkgo biloba leaves due to dissolve cellulose at high temperature 150°C [40]. However, to our knowledge, there are no reports on the extraction of cyclitol using ionic liquid aqueous solution utilizing room temperature technology.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, seeking effective and convenient separation technologies for extracting shikimic acid from plants is the emphasis and difficulty of current study. Many studies focusing on the extraction of shikimic acid have summarized the common methods, including reflux immersion, microwave assisted extraction, soxhlet extraction, ultrasound‐assisted extraction and so on . These methods have their own merits in some aspects; however, the common defects are small adsorption capacity, poor selectivity, complexity of the operation and time‐consuming.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the IL 1‐butyl‐3‐methylimidazolium chloride ([C 4 mim]Cl) is an efficient extraction solvent for shikimic acid and bilobalide from Ginkgo biloba leaves ,. Polyphenols caffeoylquinic acids were also efficiently extracted and isolated from sweet potato leaves using [C 4 mim]Cl .…”
Section: Introductionmentioning
confidence: 99%
“…However, the isolation of non‐volatile natural organic compounds such as shikimic acid and caffeoylquinic acids from the IL phase following extraction is inefficient using methodologies such as separation by anion‐exchange resin, and salting‐out and decantation techniques . Here, we utilize the insolubility of the organic solvent ethyl acetate (EtOAc) and the IL [C 2 mim][MeO(H)PO 2 ] to construct novel extraction and isolation protocols employing centrifugation and decantation techniques.…”
Section: Introductionmentioning
confidence: 99%